Doing a research project in nursing and midwifery: a basic guide to research using the literature review methodology - Siu, Carroll (Sage Publications Inc., 2013)
Due to ethical issues surrounding data collection in the field of healthcare, students are no longer able to undertake their own empirical research. This book is written for nursing and midwifery students completing a research project based on reviewing published literature and using secondary data. It de-mystifies the concept of literature review methodology and supports students writing up their dissertation, thesis or work-based learning project. The book provides step-by-step guidance on: identifying a research problem; qualitative and quantitative research design; literature searching; ethical considerations; analysis of secondary data, and writing your dissertation. Through its discussion of non-empirical methods, the book also prepares students for future empirical research by providing examples of best practice in healthcare research. The book is essential reading for undergraduates and postgraduates who want to succeed in their nursing or midwifery research project.